The Relevance of Academic Achievement to the Development of Students’ Potential and Success in Elementary Schools from the Perspective of Authentic Assessment: A Literature Study - Nursalim; Andika marsuki (International journal of technology and education research, 2025)
This study aims to analyze the relevance of academic achievement to the development of students’ potential and success in elementary schools from the perspective of authentic assessment. The background of this research lies in the continued dominance of academic grades as the main indicator of learning success, while the dimensions of process, creativity, and student character are often overlooked. The research gap stems from the lack of qualitative studies that explore the meaning, experiences, and processes of developing students’ potential through authentic assessment within the context of Indonesian elementary education. This study employs a qualitative descriptive approach using a systematic literature review of scholarly articles published between 2020 and 2025 from the Scopus, SINTA, and Google Scholar databases. Data were collected through the analysis of academic documents, educational policies, and research reports, and analyzed using thematic analysis techniques. The analysis identified four main themes: (1) a paradigm shift in assessment toward process-based evaluation, (2) the role of authentic assessment in developing students’ potential and motivation, (3) challenges in implementing authentic assessment at the elementary school level, and (4) the interconnection between academic achievement, character, and 21st-century skills. The findings indicate that authentic assessment not only enhances conceptual understanding but also fosters students’ sense of responsibility, creativity, and self-confidence. The implications of this research include the strengthening of constructivist theory in educational assessment, improving teacher competence, and formulating more holistic and humanistic assessment policies within the framework of Merdeka Belajar.